KAJIAN NORMATIF EKSISTENSI HAK ULAYAT PASCA DI UNDANGKAN UUPA NO. 5 TAHUN 1960 - SANIAH . (JURNAL ILMIAH KOHESI, 2021)
The objective of the research was to find out the existence of customary rights after the promulgation UUPA No.5 of 1960.The juricial sources were primary, secondary, and tertiary legal materials. The data were gathered by conductingdocumentary study, library research techniques are use. The research used judicial normative. The conclution of theresearch was that customary rights still recognized in article 3 of the UUPA No.5 of 1960, only that the recognition of theexistence of these customary rights is accompanied by requirements, namely as long as inreality the still exist, in accordancewith national and states interests, and must not conflict with other higher laws and regulation.